PENGEMBANGAN SISTEM PEMBELAJARAN INTERAKTIF PENGENALAN SENI DAN BUDAYA 33 PROVINSI DI INDONESIA BERBASIS WEB-GIS - Kurnia Muludi; Anie Rose Irawati; Tia Ayu Muliana (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2013)
Indonesia is an archipelago country that has a strategic geographical location with many ethnic groups. One way to preserve art and culture in Indonesia is to teach and introduce them to the next generation. Starting from elementary school children have been taught to know Indonesian arts and cultures from text books. Unfortunately, the learning is less interesting because the subjects are delivered in monotonous and conventional way. On this research, an interactive learning system is developed. The developed Web based-GIS system covers introduction of arts and cultures of 33 provinces in Indonesia. Data used in this research is obtained from art and culture book and the official website of Indonesian cultures. The system was implemented using softwares of ArcView, MapServer, MySQL database and PHP programming language. The research results showed that this learning system can provide information from each province in Indonesia based on the category selected by the user. This system can display Â information in form of pictures of traditional houses and weapons and video of the related cultures. Moreover, this system also helps students to understand more the material by usingÂ itâ€™s quiz tool.